Gender Inequality and Economic Growth in The ASEAN Region: A Panel Data Approach - Thohari, Indra Aji; Setyowati, Eni (Universitas Muhammadiyah Surakarta, 2025)
This study examines the relationship between gender inequality, trade openness, and economic growth in eight ASEAN countries (Indonesia, Malaysia, Singapore, Thailand, Philippines, Vietnam, Laos, and Cambodia) from 2010 to 2023 using a panel data approach. The estimation results indicate that the Gender Inequality Index (GII) has a significant negative impact on GDP, highlighting the importance of gender equality for economic growth. Trade openness shows a positive and significant effect, while female labour force participation (FLFP) has a positive but statistically insignificant impact. These findings emphasise that a combination of public policies promoting gender equality and open economic strategies is essential for achieving inclusive and sustainable economic growth in the ASEAN region.